The Material Composition of the Сhurochinskaya Formation in the Vishera Diamondiferous Region (Perm Krai) - E. M. Tomilina (Vestnik Permskogo Universiteta: Seriâ Geologiâ)
The results of a study of the mineral composition, structural and textural features of glacial deposits, i.e. tillites, as well as the material composition of the pelitic fraction of the Churochinskaya formation in the Krasnovisherskiy diamondiferous region are presented. Tillites were studied with petrographic and X-ray phase analysis. According to the results of petrographic study of samples of tillitic conglomerates, it was confirmed that the cementing part prevails over the detrital material. Fragments of rocks of different genesis and different sizes, but with almost the same roundness, are immersed in the main mass. The pelitic fraction of bottom sediments consists of a number of minerals: quartz, feldspar of the potassium-sodium variety, clay minerals. In most of the studied samples, clay minerals are represented by illite, occasionally accompanied by chlorite. The initial clay substance of the sediment is one of the valuable indicators of paleogeographic and paleoclimatic sedimentation environments. It is believed that the hydrous micas are formed at the first stages of hypergenesis in the weathering crusts of terrigenous rocks and sediments of the seas and oceans, where they are often found in combination with chlorite. Chlorite is one of the important indicators of sedimentation conditions.